RESEARCH OF THE MATHEMATICAL MODELS OF CONTINUOUS CAST INGOTS - R. I. Es’man; E. I. Marukovich (Литьë и металлургия, 2016)
Boundary problems of a two-dimensional temperature fields taking into account the interfaced thermal and hydrodynamic processes of formation of continuous cast ingots are developed. The numerical solution of a problem of non-steady temperature fields and temperature tension in ingots and a in the metal form in the course of their thermodiffusional interaction is received.